(untitled) (International journal of artificial intelligence, 2026)
The article examines the pedagogical foundations of teaching moving games to primary school students in the system of physical education. Particular attention is paid to the development of an effective teaching technology aimed at improving physical qualities, increasing motivation for physical activity, and forming social and communicative skills among younger schoolchildren. Moving games are considered as an important pedagogical tool for strengthening health, developing coordination, agility, speed, endurance, and fostering discipline and teamwork. The study was conducted in general secondary schools with the participation of 3rd-4th grade students. During the pedagogical experiment, the effectiveness of a specially developed methodology based on systematic game organization, age characteristics, differentiated tasks, and interactive teaching methods was evaluated. The obtained results demonstrated a significant increase in students’ physical preparedness, activity during lessons, emotional involvement, and stable interest in physical education classes. It was established that the use of modern teaching technology for moving games contributes to improving the educational process and increasing the effectiveness of physical education in primary school.